Chronic childhood undernutrition and intradomiciliary environmental factors in Taisha, Ecuador: A Scoping Review: Desnutrición crónica infantil y factores ambientales intradomiciliarios en Taisha, Ecuador: Revisión de alcance - Tsenkush-Chamik, Etsa Robinson (2026)
Introduction: Chronic childhood undernutrition in Taisha (Ecuadorian Amazon) shows alarmingly high rates. Evidence indicates that intradomiciliary environmental factors—such as dirt floors and deficits in water, sanitation, and hygiene (WASH)—are key determinants, mediated through intestinal parasitic infections. Objective: To analyze and highlight chronic childhood undernutrition and its relationship with intradomiciliary environmental factors in the Ecuadorian Amazon. Methods: A scoping review was conducted. The literature search was performed in PubMed, SciELO, and Scopus, and complemented by a search in Google Scholar. Observational studies conducted in rural and/or Indigenous pediatric populations from the Ecuadorian Amazon or comparable settings were included if they examined household flooring conditions and their association with chronic undernutrition or intestinal parasitic infections. Results: The synthesis revealed a consistent pattern: (1) Dirt floors act as reservoirs for soil-transmitted helminths and protozoa and are associated with an increased risk of infection and undernutrition. (2) This risk is synergistically amplified by limited access to safe water and inadequate sanitation. (3) In Indigenous populations, culturally mediated contact with soil represents a critical exposure pathway. Conclusion: Chronic childhood undernutrition in Taisha reflects a high-risk household environment. A comprehensive intervention is recommended, integrating floor improvement strategies, context-adapted WASH solutions, and intercultural health education. Keywords: Malnutrition; Home Environment; Soil Quality; Helminthiasis; Ecuador (Source: MeSH, NLM).